Pressure Variation and Heat Transfer in Pokka 5001 Condenser: Perubahan Tekanan dan Perpindahan Panas pada Kondensor Pokka 5001 - Rendy Rakhmad Fakhrizi; A’rasy Fahruddin; Mulyadi; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Condensers play a crucial role in thermal systems by converting steam into liquid through heat transfer processes. Specific Background The performance of condensers is influenced by key parameters such as pressure, temperature, and fluid flow rate, particularly in finned tube systems. Knowledge Gap Previous studies have examined general condenser performance, but limited research has focused on Pokka 5001 type condensers with louvered fins under varying pressure conditions. Aims This study aims to analyze the efficiency and heat transfer rate of a Pokka 5001 condenser using pressure variations as the primary variable. Results Experimental results show that increasing pressure from 20 to 40 Psi leads to higher efficiency values, ranging from 73.17% to 89.68%, and improves heat transfer rate and fluid work. Additionally, higher flow rates contribute to increased heat transfer performance. Novelty This study provides experimental evaluation of a Pokka 5001 finned tube condenser with controlled pressure variation and airflow conditions. Implications The findings support better operational control of pressure and flow rate to maintain optimal condenser performance in thermal systems. Keywords: Condenser Pressure, Heat Transfer, Efficiency Analysis, Finned Tube, Thermal System Key Findings Highlights Efficiency increases consistently with rising operating pressure Flow rate growth correlates with higher thermal transfer performance Experimental data identify optimal operating conditions